BUILDING STUDENTS’ CHARACTER ON CIVIC EDUCATION THROUGH LOCAL WISDOM OF SADRANAN - Abdul Rozaq Sholeh; Siti Sutarmi Fadhilah; Tri Murwaningsih (Universitas Muhammadiyah Ponorogo, 2019)
Sadranan is a form of cultural assimilation of Hinduism and Buddhism by Islam whose activities are clean villages and visiting residents' homes. In some places Sadranan traditions have different forms of ceremonies. Some Sadranan in other places are called